Prion–like Proteins in Plants: Key Regulators of Development and Environmental Adaptation via Phase Separation - Peisong Wu; Yihao Li (Plants)
Prion–like domains (PrLDs), a unique type of low–complexity domain (LCD) or intrinsically disordered region (IDR), have been shown to mediate protein liquid–liquid phase separation (LLPS). Recent research has increasingly focused on how prion–like proteins (PrLPs) regulate plant growth, development, and stress responses. This review provides a comprehensive overview of plant PrLPs. We analyze the structural features of PrLPs and the mechanisms by which PrLPs undergo LLPS. Through gene ontology (GO) analysis, we highlight the diverse molecular functions of PrLPs and explore how PrLPs influence plant development and stress responses via phase separation. Finally, we address unresolved questions about PrLP regulatory mechanisms, offering prospects for future research.